1987
DOI: 10.1177/10600280870211p101
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism—Drug Treatment: Part I

Abstract: The purpose of this two-part review is to explain current drug treatment in part I and discuss investigational drug therapy and miscellaneous drugs in the management of parkinsonism in part II. The medical approach to this disease is still based on the imbalance between a deficiency of dopamine and a functional increase in acetylcholine. Anticholinergic agents are used to treat the tremors in the early stages of the disease. Drug In/ell Cfin Pharm 1987;2/:10-21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 92 publications
0
3
0
1
Order By: Relevance
“…Some of the symptoms of this disease can also be alleviated by inhibiting ACh activities (Berg et al 1987). These findings also suggest that ACh-DA interactions in the striatum are important in regulating motor function.…”
Section: Functional Interactions Between Dopaminergic and Cholinergicmentioning
confidence: 95%
“…Some of the symptoms of this disease can also be alleviated by inhibiting ACh activities (Berg et al 1987). These findings also suggest that ACh-DA interactions in the striatum are important in regulating motor function.…”
Section: Functional Interactions Between Dopaminergic and Cholinergicmentioning
confidence: 95%
“…At low doses, bromocriptine acts as a pre-synaptic D2 agonist, and thereby reduces dopaminergic release and function in dopaminergically mediated systems. Its net effect at mid-range doses appears to augment the function of cerebral dopaminergic systems [13]. Passler et al (2001) [122] observed bromocriptine treatmentrelated improvements in arousal (i.e.…”
Section: Bromocriptinementioning
confidence: 99%
“…Extensive use in adults appears not to be associated with significant risks. Nausea and vomiting, orthostatic hypertension, nasal congestion, and transient hepatic enzyme elevations are the most common adverse events (29). The hallucinosis and psychotic symptoms seen when DA agonists and L-dopa are administered to patients with (usually) advanced Parkinson's disease were not seen in this pilot.…”
Section: This Pilot Of the D A Agonist Pergolide In Gts Ismentioning
confidence: 83%